2003
DOI: 10.1159/000072711
|View full text |Cite
|
Sign up to set email alerts
|

Double Resection for Patients with Pancreatic Cancer and a Second Primary Renal Cell Cancer

Abstract: Background: Reports of synchronous or metachronous double kidney-pancreas cancers are very rare. Methods: We present 2 patients with renal cell carcinoma and synchronous (1 patient) or metachronous (1 patient) primary pancreatic ductal adenocarcinoma. The patients underwent resection for both cancer types with a worthwhile outcome. Results: The appearance of different primaries in an individual may indicate a genetic predisposition to different neoplasms. The study of double primary cancers is important becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Multiple primary cancers (MPC) in the same patient are rare, but synchronous MPC are exceptional [ 1 , 2 ]. Most synchronous tumors involve both the gastrointestinal and the genitourinary tract, followed by the breast and gastrointestinal tract or the breast and genitourinary tract [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple primary cancers (MPC) in the same patient are rare, but synchronous MPC are exceptional [ 1 , 2 ]. Most synchronous tumors involve both the gastrointestinal and the genitourinary tract, followed by the breast and gastrointestinal tract or the breast and genitourinary tract [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been only infrequent reporting of synchronous or metachronous tumors of the kidney and the pancreas [ 1 , 2 , 3 , 4 ]. In 1969, Sasaki et al [ 5 ] reported the first case of an association between renal and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, only a few more case reports have been published of this coincidence with the largest group including 6 patients. Alexakis et al presented 2 patients with RCC and synchronous primary PDAC [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Second malignancies reported to be associated with renal cell carcinoma (RCC) include Non-Hodgkin’s lymphoma, multiple myeloma, chronic lymphatic leukaemia, melanoma and cancers of the bladder, prostate, breast, rectum, and lung with an incidence that varies from 5 to 27% [6,7]. There has only been infrequent reporting of synchronous or metachronous tumors of the pancreas and the kidney [5,7,8]. …”
Section: Introductionmentioning
confidence: 99%